Barriers to Physical Activity in Pregnant Women: An Explanatory Sequential Mixed-method Study (Study Protocol) - Romina Fili; Sana Nazmi; Fereshteh Behmanesh; Atefeh Omrani; Hossein-Ali Nikbakht; Leila Amiri Farahani (Iran University of Medical Sciences, 2024)
Background: Gaining insight into the obstacles holding women from engaging in physical activity during pregnancy is crucial for planning future interventions to enhance their physical activity during this period. This research aims to identify barriers to physical activity among pregnant women using an explanatory sequential mixed-methods approach. The study protocol is explained in this article. Methods: This research employs an explanatory sequential mixed-methods design. The project will be implemented in two separate phases. In the first phase, a quantitative cross-sectional study will be conducted on 358 eligible pregnant women aged 18-45 years living in Babol City, Iran. Quantitative data collection will involve using the barriers to physical activity during pregnancy scale (BPAPS) and questionnaires gathering demographic and obstetric data. The qualitative investigation will employ individual semi-structured interviews utilizing a content analysis approach. Ultimately, incorporating qualitative data will inform the interpretation of quantitative findings. Results: The results will be presented in alignment with the study objectives. Initially, the mean score of BPAPS and its subscales, along with the correlation between demographic and obstetric variables, will be reported. Subsequently, the qualitative phase will encompass the reporting of categories and the main themes. Finally, the quantitative phase findings will be interpreted, incorporating insights gained from the qualitative phase. Conclusion: Since regular physical activity during pregnancy has many benefits for maternal and fetal health, the study's findings after its implementation can play a vital role in strategic planning to address women's false beliefs and misconceptions regarding physical activity during pregnancy. In addition, this study will contribute to designing interventions to remove barriers to physical activity and encourage it in pregnant women, hence improving their overall health and well-being during pregnancy.